Radiosynthesis, In Vitro Characterization, and In Vivo PET Neuroimaging of [18F]F‑4 for Tau Protein: A First-in-Human PET Study - Lindberg, Anton; Tong, Junchao; Zheng, Chao; Mueller, Andre; Kroth, Heiko; Stephens, Andrew; Mathis, Chester A.; Vasdev, Neil (ACS chemical neuroscience, 2025)
[18F]PI-2620 is a promising radiopharmaceutical for positron emission tomography (PET) imaging of both Alzheimer’s disease (AD) and non-Alzheimer’s disease (non-AD) tauopathies in humans. An array of fluorinated derivatives of the carbazole scaffold of PI-2620 were synthesized and evaluated. In vitro binding assays with [3H]PI-2620 in human tissues with AD, progressive supranuclear palsy, and corticobasal degeneration, combined with in silico predictions of blood–brain barrier permeability, led to the selection and radiosynthesis of [18F]F-4 as a promising radiotracer. In vivo PET imaging with [18F]F-4 in healthy rats showed brain uptake and kinetics suitable for neuroimaging, similar to those of [18F]PI-2620. A first-in-human PET imaging study in a healthy subject as well as a patient with AD, in comparison with [18F]PI-2620 in the same AD subject, confirmed that [18F]F-4 is an alternative radiopharmaceutical for imaging tau protein.